Novel Technique for Comprehensive Noise Identification and Cancellation in GSM Signal - Rekha N; Fathima Jabeen (Institute of Advanced Engineering and Science, 2018)
Presence of noise significantly degrades the contents being transmitted over GSM channel. With the evolution of next generation of communication system, the challenges in noise cancellation in voice along with data transmission are not being addressed effectively by existing filters. Therefore, the proposed system offers a mechanism where emphasis is laid on identification of superior and inferior forms of GSM transient signal followed by cancellation of its noise level. Designed using analytical methodology, the proposed system harness the potential of probability theory to perform a modeling that associates allocated power of the transmitting device with the level of noise. The outcome of the study is found to offer a comprehensive identification of different forms of noise and can precisely determine the level of superior and inferior quality of signal. The outcome significantly assists in designing an accurate filter for noise cancellation in GSM signal.